Inside Cover: Beetles Do It Differently: Two Stereodivergent Cyclisation Modes in Iridoid‐Producing Leaf‐Beetle Larvae (ChemBioChem 3/2013). Issue 3 (6th February 2013) - Kunert, Maritta; Rahfeld, Peter; Shaker, Kamel H.; Schneider, Bernd; David, Anja; Dettner, Konrad; Pasteels, Jacques M.; Boland, Wilhelm
<x xml:space="preserve">Abstract</x> The inside cover picture shows a proposed mechanism for the biosynthesis of chrysomelidial in leaf‐beetle larvae. The sequence implies the formation of a dienamine intermediate that is "transoid" in P. cochleariae and "cisoid" in G. viridula. For further details see the paper by W. Boland et al. on p. 353 ff. We thank Jana Becher for the arrangement of the inside cover.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>